Role of VVZ-149, a Novel Analgesic Molecule, in the Affective Component of Pain: Results from an Exploratory Proof-of-Concept Study of Postoperative Pain following Laparoscopic and Robotic-Laparoscopic Gastrectomy. Issue 9 (24th February 2021) - Song, Inkyung; Cho, Sunyoung; Nedeljkovic, Srdjan S; Lee, Sang Rim; Lee, Chaewon; Kim, Jina; Bai, Sun Joon
Abstract: Objective: VVZ-149 is a small molecule that both inhibits the glycine transporter type 2 and the serotonin receptor 5 hydroxytryptamine 2 A. In a randomized, parallel-group, and double-blind trial (NCT02844725), we investigated the analgesic efficacy and safety of VVZ-149 Injections, which is under clinical development as a single-use injectable product for treating moderate to severe postoperative pain. Methods: Sixty patients undergoing laparoscopic and robotic-laparoscopic gastrectomy were randomly assigned to receive a 10-hour intravenous infusion of VVZ-149 Injections or placebo, initiated approximately 1 hour before completion of surgical suturing. Major outcomes included pain intensity and opioid consumption via patient-controlled analgesia and rescue analgesia provided "as needed." The treatment efficacy of VVZ-149 was further examined in a subpopulation requiring early rescue medication, previously associated with the presence of high levels of preoperative negative affect in a prior Phase 2 study (NCT02489526). Results: Pain intensity was lower in the VVZ-149 (n = 30) than the placebo group (n = 29), reaching statistical significance at 4 hours post-emergence ( P  < .05), with a 29.5% reduction in opioid consumption for 24 hours and fewer demands for patient-controlled analgesia. In the rescued subgroup, VVZ-149 further reduced pain intensity ( P  < .05) with 32.6% less opioid consumption for 24 hours compared to placebo patients. Conclusions: VVZ-149 demonstrated effective analgesia with reduced postoperative pain and opioid requirements. Consistent with the results from the previous Phase 2 study, patients with early rescue requirement had greater benefit from VVZ-149, supporting the hypothesis that VVZ-149 may alleviate the affective component of pain and mitigate excessive use of opioids postoperatively.